The Prosody of Topic Transition in Interaction: Pitch Register Variations - Riou, Marine (2017)
In conversation, speakers can mobilize a variety of prosodic cues to signal a switch in topics. This paper uses a mixed-methods approach combining Conversation Analysis and Instrumental Prosody to investigate the prosody of topic transition in American English, and analyzes the ways in which speakers can play on register level and on register span. A cluster of three prosodic parameters was found to be predictive of transitions: a higher maximum fundamental frequency (F0), a higher median F0 (key), and an expanded register span. Relative to speakers’ habitual profiles, the mobilization of such prosodic cues corresponds to a marked upgraded prosodic design. This finding is consistent with the general assumption that continuation constitutes the norm in conversation, and that departing from it, as in the case of a topic transition, requires a marked action and marked linguistic design. The disjunctive action of opening a new topic corresponds to the use of a marked prosodic cue.